2019
DOI: 10.3390/jcm8091487
|View full text |Cite
|
Sign up to set email alerts
|

The Increase of Osteoporotic Hip Fractures and Associated One-Year Mortality in Poland: 2008–2015

Abstract: Introduction: Hip fractures are a worldwide public health issue associated with significant mortality. Previous Polish studies reported an increasing trend in the number of hip fractures for both men and women, although lower than most other European countries. Materials and Methods: The Polish National Database was analyzed to examine osteoporotic hip fractures in the population aged 50 and over. Hip fracture incidence, rate, one-year mortality, and postoperative length of hospitalization were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
1
18
0
5
Order By: Relevance
“…In addition, indicators of osteoporosis such as bone density or imaging information are seldom available in the medical insurance databases. Therefore, consistent with previous publications on hip fracture incidence [8,9,11,16,29], in this study, hip-fracture-related indicators such as the incidence of hip fracture and associated costs in patients aged 55 years and above were used as surrogate indexes for determining the burden of osteoporosis or osteoporotic fractures. The inclusion criteria of the population were individuals who (1) had either UEMBI or URBMI during 2012 to 2016, (2) were enrolled in UEMBI or URBMI in 1 of the 23 provinces included in the study, and (3) were �55 years old at the first hip fracture during the study period.…”
Section: Study Populationmentioning
confidence: 82%
“…In addition, indicators of osteoporosis such as bone density or imaging information are seldom available in the medical insurance databases. Therefore, consistent with previous publications on hip fracture incidence [8,9,11,16,29], in this study, hip-fracture-related indicators such as the incidence of hip fracture and associated costs in patients aged 55 years and above were used as surrogate indexes for determining the burden of osteoporosis or osteoporotic fractures. The inclusion criteria of the population were individuals who (1) had either UEMBI or URBMI during 2012 to 2016, (2) were enrolled in UEMBI or URBMI in 1 of the 23 provinces included in the study, and (3) were �55 years old at the first hip fracture during the study period.…”
Section: Study Populationmentioning
confidence: 82%
“…suggested that hip fracture rates may be increasing in Poland [3], France [4], Japan [5], Italy [6], and China [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, studies show a variation of the mortality rate ranging from 2.8% in elderly people with multiple injuries in Curitiba (State of Paraná) [3] to 28.7% in the elderly people with hip fractures in Porto Alegre (State of Rio Grande do Sul) [18]. Studies worldwide report a mortality rate of 37.2% in hospitalized elderly patients with hip fractures in Turkey [4], 30% in Poland [19], 11.4% in Spain [20], and 12.3% in elderly with axis fractures in USA [21]. Wide variation can be attributed to the diversity of the populations and the fractures admitted to hospitals and probably reflects the different standards of care provided at these institutions.…”
Section: Discussionmentioning
confidence: 99%